2020
DOI: 10.1101/2020.03.14.992172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxytocin differentially modulates amygdala responses during top-down and bottom-up aversive anticipation

Abstract: The ability to successfully regulate negative emotions such as fear and anxiety is vital for mental health.The neuropeptide oxytocin (OXT) acts as important modulator of emotion regulation, as reflected by reduced amygdala responses but increased amygdala-prefrontal cortex (PFC) functional connectivity in response to threatening stimuli. The present randomized, between-subject, placebo (PLC)controlled pharmacological study combined intranasal administration of OXT with functional MRI during an explicit (cognit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 127 publications
(143 reference statements)
0
22
1
Order By: Relevance
“…This allowed us to compare the activity of individual brain networks in different groups [50]. Previous studies have indicated that the effect of OT on brain activity is modulated by emotional state and individual variability [51,34,52]. Thus, we measured whether OT could affect the associations between brain network activation and subjective emotional states as well as personality traits.…”
Section: Predictive Modelmentioning
confidence: 99%
“…This allowed us to compare the activity of individual brain networks in different groups [50]. Previous studies have indicated that the effect of OT on brain activity is modulated by emotional state and individual variability [51,34,52]. Thus, we measured whether OT could affect the associations between brain network activation and subjective emotional states as well as personality traits.…”
Section: Predictive Modelmentioning
confidence: 99%
“…For instance, accumulating evidence from basic research and proof-of-concept studies suggests that targeting hormonal systems such as the oxytocin or vasopressin system may have the potential to facilitate social functioning in relevant domains in both, healthy individuals as well as patients with mental disorders [99]. A single intranasal dose of oxytocin reduced aversive anticipation in high anxious individuals [100] and prevented sensitization towards angry faces [101] via reducing amygdala reactivity. Furthermore, oxytocin was found to enhance approach behavior towards positive social stimuli by modulating responsivity of the anterior insula [102,103].…”
Section: Mechanismsmentioning
confidence: 99%
“…Poldrack et al, 2017; Woo et al, 2017) and ‘classical’ neuroimaging indices of fear reduction such as pharmacologically attenuated amygdala reactivity have been observed during several paradigms including threat conditioning and extinction, aversive anticipation, general negative affect but also various social processes such as face processing or social sharing (e.g. Geng et al, 2018; Ma et al, 2018; Paulus et al, 2021; Xin et al, 2020). Together with studies reporting intact fear and anxiety experience in patients with complete bilateral amygdala damage (Anderson & Phelps, 2002; Becker et al, 2012; Mihov et al, 2013) and studies reporting fear and anxiety decreases in the absence of effects on amygdala activation (e.g.…”
Section: Introductionmentioning
confidence: 99%